Experiência de cárie dentária em pacientes fissurados e não fissurados de uma instituição hospitalar universitária: estudo de caso-controle - Mânica, Maíra Fernanda Michelin (2023)
Case-control study of a university hospital population base with age-matched groups. The objective was to investigate the experience of tooth decay in cleft and non-cleft patients at a university hospital institution: a case-control study. The sample comprising 121 patients aged between 0 and 18 years were included in the study. Patients with non-syndromic cleft lip and/or palate (n=60) were recruited from the Center for Attention and Research in Craniofacial Anomalies (CEAPAC) at the Hospital Universitário do Oeste do Paraná (HUOP) and non-cleft controls (n=61) at the HUOP Pediatrics Outpatient Clinic. Both Centers are located in the municipality of Cascavel, in the western region of Paraná, Brazil. Demographic data were collected from an interview and a clinical examination was carried out to assess the dental condition and aspects related to the cleft. There was a statistical difference between the case and control groups for the dmft/DMFT variable. The mean dmft/DMFT value of the case group (3.55) was above that of the control group (2.24). According to the Odds Ratio analysis, the cleft group had a 1.6 × greater chance of developing tooth decay when compared to the control group, which was statistically significant. There was no statistical difference between the groups for the variables presence of untreated caries, level of dental health and need for treatment. It was concluded that cleft patients had a greater experience of caries when compared to the control group.